1969
DOI: 10.1128/jvi.4.5.554-566.1969
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Precursors into Ribonucleic Acid, Protein, Glycoprotein, and Lipoprotein of Avian Myeloblastosis Virions

Abstract: Freshly explanted leukemic myeloblasts produce avian myeloblastosis virus (AMV) at a constant rate without any obvious cytopathic effect; therefore, subviral components are continually synthesized at a steady rate. The incorporation of various radioactive precursors into virions was monitored by determination of radioactivity in purified virus after density equilibrium sedimentation in preformed sucrose gradients. The kinetics of incorporation of 3H-uridine have shown that there is an average time interval of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Secondly, the time of virus protein production and the appearance of infectious virus indicated that the interval between the manufacture of these three structural proteins and their incorporation into infectious virus must be quite short. This is also in agreement with the timing of avian oncornavirus production in the presence of some inhibitors of macromolecular synthesis (1).…”
Section: Figsupporting
confidence: 87%
See 1 more Smart Citation
“…Secondly, the time of virus protein production and the appearance of infectious virus indicated that the interval between the manufacture of these three structural proteins and their incorporation into infectious virus must be quite short. This is also in agreement with the timing of avian oncornavirus production in the presence of some inhibitors of macromolecular synthesis (1).…”
Section: Figsupporting
confidence: 87%
“…DNA synthesis was performed in petri dishes of both depleted normal and MLV-infected cells. The rate of uptake of [3 H]thymidine (New England Nuclear Corp.), 1 MCi/dish in 1 ml, was measured as the counts per minute of precursor rendered acid insoluble after 1 h of incubation at 37 C, and expressed as activity/105 cells (5). Cells in mitosis were counted in sparsely seeded cultures.…”
Section: Methodsmentioning
confidence: 99%
“…macromolecules (3,6) and suggest that these molecules can be utilized for terminal steps in assembly under conditions of severely restricted viral RNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In tissue culture it was demonstrated that when a cell was infected with an RNA tumor virus, the Rous sarcoma virus, the characteristic changes produced in the cell by the virus could be inhibited by inhibiting DNA synthesis (TEMIN 1968). Also it was demonstrated in tissue culture that the production of RNA tumor viruses are sensitive to actinomycin D (TEMIN 1963;BALUDA and NAYAK 1969), a substance which inhibits transcription of DNA; and finally, cells transformed in culture by RNA tumor viruses contain new DNA which hybridizes with viral RNA (TEMIN 1964). It was these tissue culture experiments that led Temin and Baltimore to their very fine observations in the cell free system.…”
Section: Karyotypes Of 5 Cells From the Aedes Aegypri Cell Line Demonmentioning
confidence: 99%